KERUKUNAN BERAGAMA PERSPEKTIF PARA PEMUKA AGAMA DAN KEPERCAYAAN DI KARANGROWO KUDUS - Alifa Fidiyawati; Ulya Ulya (Balai Penelitian dan Pengembangan Agama Semarang, 2019)
Religious diversity in plural society tends to have the potential for conflict over the differences they have. In several regions in Indonesia there have been also conflicts due to the diverse religions and beliefs. But in Karangrowo, Undaan-Kudus, people live in harmony. This article discusses the concept of harmony according to religious leaders (Muslim clerics/kyai & priests) and teachers of faith believers ‘Sedulur Sikep’ in Karangrowo, Undaan Kudus and its implementation. This study is a field research with a qualitative approach and data were collected from religious leaders, faith believer teachers and elements of village government through interviews, observation, and documentation. The results of the study found that religious leaders (Muslim clerics & priests) and faith believer teachers ‘Sedulur Sikep’ in Karangrowo Village serve as interpreters of religious teachings about harmony and make it easier to be understood by people. Muslim clerics emphasize the Islamic universal values of mercy (rahmah) and brotherhood (ukhuwah). Christian priests assert in the love of Jesus which must be spread to all people. While for the ‘Sedulur Sikep’ teachers, they stress on the attitudes in life such as living in fresh and healthy life (seger waras), peace and harmony (guyub rukun), and doing good in day and night (nglakoni apik sak rinane sak wengine). The teachings of those religious leaders are implemented by both religious communities and faith believers followers in behavior and religious and social activities.